Relationships between Molina’s hog nosed skunks, Conepatus chinga (Mammalia, Mephitidae) and human beings in the Chaupihuaranga river basin, Pasco, Peru - Daniel Cossios, E. (2018)
Throughout the skunks' distribution range, several kinds of conflicts between these animals and human beings have been recorded. In Peru, although these issues seem to be common, records thereof have been merely anecdotal. Here we describe, for the first time, the relationships between people and skunks in a Peruvian area. The study was conducted in five villages of the Chaupihuaranga River basin, in Pasco department. Interviews were made to collect information about people's attitude toward Molina's hog-nosed skunks, the uses given to this animal, hunting methods and number of hunted skunks. Almost all interviewees (97.8%) considered skunks as harmful animals and the majority (87%) admitted hunting them. Skunks are mainly hunted to control the damage they cause to the crop fields, but they are also used as food, in traditional medicine and to make decorative elements. Two hunting modalities were reported: hunting following casual encounters and organized hunting by crop field keepers. The skunk skins are displayed at the homes of the hunting crew leaders, giving prestige to them. Genetic analyses performed on skin samples suggested stability or recent population growth. Both controlling skunk population to limit the damage they cause to the crop fields and using this species in traditional medicine seem to be ancestral activities. Although skunk hunting in the study area seems to be sustainable, we recommend conducting evaluations of skunk populations to verify whether hunting entails a risk factor for their conservation.